Role of Data Mining in the Manufacturing and Service Application (International Journal of Engineering and Computer Science, 2014)
In the today scenarios, the manufacturing and service industries are focusing on the highly effective tools which are mainly concentrated over the data mining. Several organisations and researchers have accomplished their efforts in the reviewing of the data mining tools and the surveying the data miners. In this present paper, the notion of machine learning and the data mining in the various manufacturing and service application is introduced. On the result, the idea of building the decision making systems are more clear as the algorithms of the machine learning helps in extracting the knowledge from the databases which are in the diverse form. As in the case where the operational engineering data is based, we can determine the optimal control parameters, faults detection in the equipment. So, the framework is designed which uses constructs such as decision maps, decision tables, etc. for the decision making system that helps in applying and organizing knowledge in the manufacturing and service application